2022
DOI: 10.1186/s12935-021-02428-3
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis biomarkers based on m6A-related lncRNAs for myeloid leukemia patients

Abstract: Background Chronic myeloid leukemia (CML) and acute myeloid leukemia (AML) are two common malignant disorders in leukemia. Although potent drugs are emerging, CML and AML may still relapse after the drug treatment is stopped. N6-methyladenosine (m6A) and lncRNAs play certain roles in the occurrence and development of tumors, but m6A-modified LncRNAs in ML remain to be further investigated. Methods In this study, we extracted and analyzed the TCGA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…There is one azacytidine and B-cell lymphoma/leukemia-2 inhibitor combined with thalidomide for the treatment of clinically advanced MDS, CMML, and AML. The results of the phase II study [ 21 23 ] ORR was 63.0%, the overall survival was 28.1 months, and the nonhematotoxicity was grade III or higher 85.0%, indicating that combination therapy is good and that treatment is tolerated. This paper is consistent with the conclusions of relevant foreign studies, and all reflect the combination of azacytidine and B-cell lymphoma/leukemia-2 inhibitors with good efficacy, but the drug toxicity is greater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is one azacytidine and B-cell lymphoma/leukemia-2 inhibitor combined with thalidomide for the treatment of clinically advanced MDS, CMML, and AML. The results of the phase II study [ 21 23 ] ORR was 63.0%, the overall survival was 28.1 months, and the nonhematotoxicity was grade III or higher 85.0%, indicating that combination therapy is good and that treatment is tolerated. This paper is consistent with the conclusions of relevant foreign studies, and all reflect the combination of azacytidine and B-cell lymphoma/leukemia-2 inhibitors with good efficacy, but the drug toxicity is greater.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis showed that the use of azacytidine and B-cell lymphoma/leukemia-2 inhibitors was associated with an increased risk of decreased neutrophil counts and platelet counts in patients with MDS/AML, and that azacytidine and B-cell lymphoma/leukemia-2 inhibitors did not significantly increase high anemia, leukopenia, or febrile neutrality compared with traditional supportive care risk of agranulocytosis [ 22 ]. In this study, 3 cases of renal function impairment and 7 cases of liver function damage appeared, and foreign studies found that adverse reactions such as elevated serum creatinine occurred during the application of azacytidine and B-cell lymphoma/leukemia-2 inhibitors; so, biochemical indicators such as liver and kidney function should be closely monitored during the chemotherapy process [ 23 ]. Nonhematogenousness is found to cause patients to develop symptoms of the heart system, mainly manifested as left ventricular failure, arrhythmias, hypertension, myocardial infarction, and angina.…”
Section: Discussionmentioning
confidence: 99%
“…CHROMR has also been implicated in elevated risk for stomach adenocarcinoma ( Luo et al, 2022 ), lung adenocarcinoma ( Bai et al, 2022 ), increased resistance to chemotherapy in Lymphoma ( Wang et al, 2022 ), but also in antiviral response to Influenza and COVID-19 infections ( van Solingen et al, 2022 ) and autoimmune disease, such as multiple sclerosis ( Teimuri et al, 2018 ). CHROMR expression is different when comparing lymphoid cancer (high) with myeloid cancer (low) cell lines ( Yang et al, 2022 ). Our results suggest that increased CHROMR expression could be linked to development of malignancy and poorer prognosis for brain glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, detecting m 6 A modification levels in lncRNA helps evaluate the prognostic level of patients with acute and chronic myelogenous leukemia. 97 , 98 …”
Section: Rna Modifications In the Tumor Microenvironmentmentioning
confidence: 99%